Selfregulation â€" the key to progress in clinical reasoning - T Postma (South African Medical Association, 2015)
Background. In 2009 a new case-based instructional design was implemented during the preclinical year of study of the undergraduate dental curriculum of the University of Pretoria, South Africa. The objective of the educational intervention was to improve the development of clinical reasoning skills. To achieve this, systematic scaffolding, relevance, integration and problem-solving were actively promoted as part of teaching and learning. A studentâ€™s clinical reasoning was measured by a progress test containing 32 multiple choice questions (MCQs), formulated on a knowledge application level. In 2011 it became clear that some students showed progression while others did not. Objectives. This study was conducted to gauge the value of the case-based intervention with the aim of determining the need for further scaffolding and support, especially for non-progressing students. Methods. The 2011 BChD IV cohort (N=48) was identified for the study. Two semi-structured focus group discussions were conducted. Group 1 (n=8) consisted of students who progressed â‰¥9%, while group 2 (n=8) comprised students who did not progress to the same extent. Results. Both groups lauded the scaffolding that the case-based curriculum provided. Strategic thinking, goal orientation and self-regulation ability were identified in group 1. A lack of diligence, poor data-processing ability and a possible lack of interest were identified in group 2 students, who were unaware of learning opportunities. Conclusion. There is a need for early identification of students lacking self-regulated learning and for providing timely feedback and support to progressively develop their clinical reasoning skills.